STEROIDAL SAPOGENINS 164 NOLOGENINANDITS DE GRADATION PRODUCTS - MARKER, RE; LOPEZ, J (BOTANICA-MEX S. A, TEXCOCO, EM, MEX, 1947)
Nolonin has been isolated from Dioscorea mexicana. Mild hydrolysis gives nologenin. Strong acid hydrolysis gives kryptogenin. Methanolic hydrochloric acid on nolonin, nologenin, pennogenin and kryptogenin gives bethogenin. Mild acid treatment of nologenin
J OPT SOC AM
Keywords: STEROIDAL SAPOGENINS. 164., NOLOGENINANDITS, GRADATION PRODUCTS; QUIMICA; QUIMICA INORGANICA; QUIMICA DE LOS PIGMENTOS